2013
DOI: 10.1161/circep.111.000104
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leptin Signaling in the Pathogenesis of Angiotensin II–Mediated Atrial Fibrosis and Fibrillation

Abstract: The online-only Data Supplement is available at http://circep.ahajournals.org/lookup/suppl/doi:10.1161/CIRCEP.111.000104/-/DC1. Correspondence to Naohiko Takahashi, MD, PhD, Department of Laboratory Examination and Diagnostics, Oita University Faculty of Medicine, 1-1 Idaigaoka, Hasama, Oita 879-5593, Japan. E-mail takanao@oita-u.ac.jp Background-We examined the hypothesis that leptin signaling contributes to the atrial fibrosis and atrial fibrillation (AF) evoked by angiotensin II (AngII). Methods and Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 30 publications
3
73
1
3
Order By: Relevance
“…One study looking at the role of leptin in AF pathogenesis in mice, demonstrated that leptin-deficient knockout mice did not develop atrial interstitial fibrosis and subsequent AF inducibility in response to infusions of angiotensin-II compared with controls 32. These findings suggested that leptin could play a role in the pathogenesis of atrial fibrosis seen in certain patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…One study looking at the role of leptin in AF pathogenesis in mice, demonstrated that leptin-deficient knockout mice did not develop atrial interstitial fibrosis and subsequent AF inducibility in response to infusions of angiotensin-II compared with controls 32. These findings suggested that leptin could play a role in the pathogenesis of atrial fibrosis seen in certain patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies examining the effects of cell-specific modulation of leptin signaling may contribute to our understanding of the role of endogenous leptin in obesity-associated cardiac remodeling. In addition to its effects on cardiomyocytes, leptin modulates fibroblast phenotype, activating a fibrogenic program (109). Whether fibroblast-specific effects of leptin mediate myocardial fibrosis in obesity has not been rigorously tested.…”
Section: The Molecular Signals Regulating Obesity-associated Fibrosismentioning
confidence: 99%
“…10, 11 Atrial inflammatory profibrotic signals induce interstitial atrial fibrosis, which plays a critical role in AF pathogenesis. [12][13][14] For instance, hypertension-characterized by pressure overload-stimulates inflammatory profibrotic signals, leading to enhanced vulnerability to AF; [15][16][17][18][19][20][21] indeed, hypertension is a major risk factor for AF. 22 However, the role of the spleen and IL-10 in inflammatory atrial fibrosis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%